Synthesis and characterization of pvdf/nacl membrane for ammonia removal from aquaculture - Chiam, Chel Ken (2011)
In this study, polyvinylidene fluoride (PVDF) flat membrane was fabricated to remove the total ammonia from saline water by direct contact membrane distillation (DCMD) at 50oC. The effects of initial NH 3 concentration from 0.03 to 0.47M, temperature from 30 to 50oC and salinity from 0 to 35ppt on ammonia-ammonium equilibrium, however, were initially investigated by using Law of Ostwald’s Dissociation. The PVDF membranes were then fabricated from dimethylacetamide (DMAc) solvent and sodium chloride (NaCl) from concentration 0 to 6M as the dope additive by phase inversion in a distilled water coagulation bath. The membranes were dried and then characterized as well as applied in DCMD. Cocurrent configuration of DCMD was applied to study the mass transfer, water vapor flux and ammonia removal efficiency of the membranes. The experimental results showed the NH 3 concentration in the water increases as the temperature and pH increased. The NH 3 concentration, however, is relatively higher in pure water than that in saline water from temperature 30 to 50oC. The drying process has improved the hydrophobicity of the membranes. The contact angles of the membranes with NaCl addition, however, were reduced from 165 to 156o. Graphically, the average ranges of membrane thickness and pore size were 71.5 to 111.5μm and 43.5 to 118.5nm, respectively. The addition of NaCl has reduced the average pore size from 81 to 66nm. Statistically, average ranges of the membrane thickness and pore size were 83 to 99μm and 82 to 103.3nm, respectively. The average membrane porosity with additives were increased from 78% to >82% compared to that of without the additives. The mass transfer coefficient of ammonia and the water vapor flux increase as the membrane porosity increased. The membrane porosity of 84% and effective membrane area of 56.40cm2 achieved the highest ammonia removal efficiency about 24% within 2 hours of DCMD.